Inovasi Desain Busana Berdasarkan Kombinasi AI dan Teknik Slashing - Inovasi, Efisiensi, dan Keberlanjutan - Wiwid Wahyudi; Irdha Yunianto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Innovation in the fashion industry is increasingly influenced by the integration of technology, which plays a crucial role in creating more efficient and sustainable design practices. This study explores the potential of combining fabric slashing techniques with artificial intelligence (AI) to optimize the design process, reduce textile waste, and support sustainability goals. Using a mixed-methods approach, the study involved experimentally developing an AI-based algorithm capable of automatically generating cutting patterns. Surveys and in-depth interviews with fashion designers provided qualitative insights into the acceptance, feasibility, and challenges of adopting this technology in a real-world design environment. The results indicate that integrating AI into cutting techniques reduced textile waste by up to 25%, while accelerating the design process and enabling the creation of more complex and innovative patterns compared to traditional manual methods. Furthermore, designers reported that the AI-based system not only increased efficiency but also expanded creative opportunities by presenting previously unimaginable design alternatives. The study also highlights the broader implications of AI applications in fashion innovation, particularly in adapting industry practices to global sustainability demands. By reducing waste and encouraging smarter production systems, AI has the potential to catalyze the transformation of the fashion industry towards an environmentally friendly and resource-efficient sector. The results of this study reinforce the importance of implementing cutting-edge technologies in response to growing environmental concerns and market demand for sustainable fashion. This research also makes a significant contribution to the development of modern design approaches by presenting empirical evidence of the synergistic benefits of traditional techniques and digital intelligence, while also offering practical recommendations for designers, researchers, and industry stakeholders to utilize AI as a strategy in building a sustainable fashion ecosystem that balances creativity, efficiency, and environmental responsibility.